A non-linear two-dimensional float gate transistor as a lateral inhibitory synapse for retinal early visual processing. Issue 9 (12th July 2022) - Hu, Man; Yu, Jun; Chen, Yangyang; Wang, Siqi; Dong, Boyi; Wang, Han; He, Yuhui; Ma, Ying; Zhuge, Fuwei; Zhai, Tianyou
Abstract : A bidirectional rectifying transistor was presented based on MoS2 /h-BN/graphene heterostructure, which in a two-dimensional array could emulate the key lateral inhibition function of horizontal cells in retina and enable early vision processing. Abstract : Synaptic transistors that accommodate concurrent signal transmission and learning in a neural network are attracting enormous interest for neuromorphic sensory processing. To remove redundant sensory information while keeping important features, artificial synaptic transistors with non-linear conductance are desired to apply filter processing to sensory inputs. Here, we report the realization of non-linear synapses using a two-dimensional van der Waals (vdW) heterostructure (MoS2 /h-BN/graphene) based float gate memory device, in which the semiconductor channel is tailored via a surface acceptor (ZnPc) for subthreshold operation. In addition to usual synaptic plasticity, the memory device exhibits highly non-linear conductance (rectification ratio >10 6 ), allowing bidirectional yet only negative/inhibitory current to pass through. We demonstrate that in a lateral coupling network, such a float gate memory device resembles the key lateral inhibition function of horizontal cells for the formation of an ON-center/OFF-surround receptive field. When combined with synaptic plasticity, the lateral inhibition weights are further tunable to enable adjustable edge enhancement for early visual processing. Our results here hopefully open a new scheme toward early sensory perception via lateral inhibitory synaptic transistors.